Endoscopic and pathohistologic features of early gastric signet ring cell carcinoma presented as elevated type: A case report - Di, Lianjun; Wu, Xinglong; Tuo, Biguang (Frontiers in Oncology, 2022)
Background: Almost all early gastric signet ring cell carcinomas (SRCC) are flat or depressed type, and the elevated type is rare. Here we report the endoscopic and pathohistologic features of a rare case of SRCC presented as elevated type. Case presentation: A 54-year-old male underwent esophagogastroduodenoscopy in our hospital because of intermittent upper abdominal pain for 6 years. White light endoscopy revealed an elevated lesion with a smooth and reddish, covered with normal mucosa, and looked like polyps. Magnifying endoscopy with narrow-band imaging showed broadened intervening parts, elongated pit and dense microvascular network with focal irregularity. The lesion was considered as early gastric cancer and completely resected with endoscopic submucosal dissection. Pathohistological examination confirmed that the lesion was pure early SRCC which was limited within the mucosal lamina propria (T1a). Conclusion: Elevated pure gastric SRCC is rare. This is a report of early pure gastric SRCC presented as elevated type and description of its endoscopic and pathohistologic features, which will contribute to early detection of gastric SRCC.